Improvement of black locust (Robinia pseudoacacia L.) growing under marginal site conditions in Hungary: case studies - Rédei, Károly; Keserű, Zsolt; Csiha, Imre; Rásó, János; Bakti, Beatrix; Takács, Marianna (Acta Agraria Debreceniensis, 2018)
In Hungary, black locust (Robinia pseudoacacia L.) is considered as an important exotic stand-forming tree species growing mostly under unfavourable ecological conditions for forest management. Due to climate change effects, its importance is increasing in many other countries, too. As a result of a selection programme, new black locust clones were tested in clone trials. Juvenile growth of 12 micropropagated black locust clones in two plots series established at different dates were evaluated in central Hungary under marginal site conditions. At age of 7 the clone R. p. ‘Bácska’ (‘KH 56A2/5’), at age of 10 the clones R.p. ‘Homoki’ (‘MB17D3/4’) and ‘PV201E2/4’ appeared to be especially promising for mass production. Based on the data obtained from the performed trials, it can also be concluded that tissue culture can be considered as a suitable tool for propagating superior individuals and offers new prospects for the rapid cloning of selected genotypes used for plantation forestry.